Use of gemtuzumab ozogamicin in relapsed refractory acute myeloid leukemia: Multi-center real life data from Turkey. (2021) - Küçükdiler, Ayşe Hilal Eroğlu; Yavaşoğlu, İrfan and Selim, Cem and Mutlu, Cansu Atmaca and Karakuş, Abdullah and Koyuncu, Mahmut Bakır and Bilgir, Oktay and Ayyıldız, Orhan and Tiftik, Eyüp Naci and Bolaman, Ali Zahit
Abstract: We retrospectively evaluated the use of gemtuzumab ozogamicin (GO) in relapsed refractory (R/R) acute myeloid leukemia (AML) patients. Twenty-one CD33 positive R/R AML patients who received GO as a single agent in 4 hematology centers were included in this study. The median age was 59, and the median ECOG performance score was 2. According to cytogenetic analysis, 1 patient had favorable risk, 12 patients with intermediate, and 8 patients with adverse risk. The overall response rate was 52.3%. Partial response was achieved in 3 of 8 patients with adverse risk. 33.3% of patients developed grade 3 anemia. Grade 4 neutropenia and thrombocytopenia were observed in 80% of the patients. One of the patients died due to sinusoidal obstruction syndrome / veno-occlusive disease (SOS / VOD) due to GO side effects. GO may be considered as a good option for salvage therapy in R/R AML patients.